2010
DOI: 10.1016/j.febslet.2010.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Induction of growth arrest by miR‐542‐3p that targets survivin

Abstract: Edited by Tamas DalmayKeywords: MicroRNA miR-542-3p Cell cycle arrest Survivin 18S ribosomal RNA a b s t r a c t Survivin is a protein which functions as a mitotic regulator as well as apoptosis inhibitor. In this study, we show that introduction of synthetic miR-542-3p mimetic reduced both mRNA and protein levels of survivin. In A549 cells, luciferase reporter assay revealed that miR-542-3p targeted predicted binding sites in the 3 0 -untranslated region (3 0 -UTR) of survivin. We also demonstrate that ectopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
61
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 20 publications
4
61
0
Order By: Relevance
“…A previous study showed that miR-542-3p was downregulated in matched ectopic endometrium compared to eutopic and normal endometrium (NE), implicating it in the pathogenesis of endometriosis (Toloubeydokhti et al, 2008). More recently, miR-542-3p was shown to target survivin and inhibit proliferation by inducing cell cycle arrest, suggesting a potential role for miR-542-3p in control of human cancer growth (Yoon et al, 2010). However, survivin is an evolutionarily non-conserved target of miR-542-3p, and it did not serve as a target in c-Srctransformed mouse embryonic fibroblasts (Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study showed that miR-542-3p was downregulated in matched ectopic endometrium compared to eutopic and normal endometrium (NE), implicating it in the pathogenesis of endometriosis (Toloubeydokhti et al, 2008). More recently, miR-542-3p was shown to target survivin and inhibit proliferation by inducing cell cycle arrest, suggesting a potential role for miR-542-3p in control of human cancer growth (Yoon et al, 2010). However, survivin is an evolutionarily non-conserved target of miR-542-3p, and it did not serve as a target in c-Srctransformed mouse embryonic fibroblasts (Supplementary Figure S2).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study used a bioinformatic search (TargetScan) and a microarray analysis to identify the potential miR-542-3p target genes (Yoon et al, 2010). Among the predicted targets, survivin, a member of the inhibitor of apoptosis family, was shown to be a direct target of miR-542-3p in a human cancer cell line.…”
Section: Ilk Is a Conserved Target Of Mir-542-3pmentioning
confidence: 99%
See 1 more Smart Citation
“…Aberrant expression of microRNAs has been identified to play roles of oncogenes or suppressors in various human cancers (19 -21), showing promising therapeutic potential for anticancer strategies (22,23). It has been reported that miR-542-3p, which is located in Xq26.3, is down-regulated in non-small cell lung cancer and breast cancer and directly targets survivin or angiopoietin-2, respectively, leading to growth arrest and angiogenesis inhibition (24,25). In the current study, we report that in astrocytoma down-regulation of miR-542-3p was significantly associated with histopathological grading and poor patient prognosis of the disease.…”
mentioning
confidence: 99%
“…As miR-542-3p has been proposed and validated to target Table 6 Myometrial micro-RNAs (miRNAs), their expression regulation, proposed function, and transcriptional targets. The role of micro-RNAs in the female reproductive tract survivin and suppress cell growth (Yoon et al 2010), the potential role of this miRNA in the pathogenesis of leiomyomas is unclear at this time. miR-498 has been proposed to target ZEB2 (based on upon TargetScan analysis).…”
Section: Uterus: Myometriummentioning
confidence: 99%